The pH and thermal response of purified leucine-specific aminopeptidase from aeromonas caviae (2008)
A purified extracellular monomeric leucine-specifìc aminopeptidase from Aeromonas caviae T-58 with molecular mass of 32 kDa was subjected to varying pH and temperature conditions to determine its response. The activity of the enzyme was maximal at 65°C but stable up to 40°C. Optimum pH was 8.0 and pH stability had a range of 6 and 10.